Open Discussion Forums and Effective Group Division for Improved Student Engagement in Teaching Learning Process - Manojkumar, Rampelli; Krishnan, Sivakumar (Journal of Engineering Education Transformations, 2025)
Open discussion forums are increasingly recognized as a key strategy for enhancing student engagement in higher education. These forums foster interaction, critical thinking, and knowledge retention by allowing students to collaborate and solve problems together. The effectiveness of such forums largely depends on how groups are structured, with various methods like homogeneous, heterogeneous, and interest-based grouping offering different benefits. This paper presents a case study involving second-year electronics and communication engineering students at BVRIT HYDERABAD College of Engineering for Women and demonstrates that strategic group division, combined with activities like open book tests and Q&A sessions, significantly improved student performance and engagement, particularly in understanding complex concepts. This approach has proven especially beneficial for diverse learners, making it a promising method for boosting academic outcomes in higher education.